Tobacco, alcohol, and p53 overexpression in early colorectal neoplasia - Terry, Mary Beth (BioMed Central, 2003)
BACKGROUND: The p53 tumor suppressor gene is commonly mutated in colorectal cancer. While the effect of p53 mutations on colorectal cancer prognosis has been heavily studied, less is known about how epidemiologic risk factors relate to p53 status, particularly in early colorectal neoplasia prior to clinically invasive colorectal cancer (including adenomas, carcinoma in situ (CIS), and intramucosal carcinoma). METHODS: We examined p53 status, as measured by protein overexpression, in 157 cases with early colorectal neoplasia selected from three New York City colonoscopy clinics. After collecting paraffin-embedded tissue blocks, immunohistochemistry was performed using an anti-p53 monoclonal mouse IgG(2)a [BP53-12-1] antibody. We analyzed whether p53 status was different for risk factors for colorectal neoplasia relative to a polyp-free control group (n = 508). RESULTS: p53 overexpression was found in 10.3%, 21.7%, and 34.9%, of adenomatous polyps, CIS, and intramucosal cases, respectively. Over 90% of the tumors with p53 overexpression were located in the distal colon and rectum. Heavy cigarette smoking (30+ years) was associated with cases not overexpressing p53 (OR = 1.8, 95% CI = 1.1–2.9) but not with those cases overexpressing p53 (OR = 1.0, 95% CI = 0.4–2.6). Heavy beer consumption (8+ bottles per week) was associated with cases overexpressing p53 (OR = 4.0, 95% CI = 1.3–12.0) but not with cases without p53 overexpression (OR = 1.6, 95% CI = 0.7–3.7). CONCLUSION: Our findings that p53 overexpression in early colorectal neoplasia may be positively associated with alcohol intake and inversely associated with cigarette smoking are consistent with those of several studies of p53 expression and invasive cancer, and suggest that there may be relationships of smoking and alcohol with p53 early in the adenoma to carcinoma sequence.